2008
DOI: 10.1167/iovs.07-0899
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on Torsional Optokinetic Nystagmus

Abstract: tOKN appears to fail increasingly with age, in contrast to previous reports of horizontal and vertical OKN systems. This indicates that the ability to respond to rotary motion is more sensitive to the effects of aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Other reports have also documented abnormalities in OKN function (increased latency to circular vection, increased rate of OKN asymmetry, and decreasing torsional OKN) with advancing age. 19,53,65 Finally, Calder provides a good summary on the effects of aging for various ocular motor tests from numerous published reports, which are summarized in Table 1. 52 Overall, prolonged saccadic latencies and reduced smooth pursuit and OKN gains are observed in elderly patients when compared against younger adults.…”
Section: Ocular Motor Testingmentioning
confidence: 99%
“…Other reports have also documented abnormalities in OKN function (increased latency to circular vection, increased rate of OKN asymmetry, and decreasing torsional OKN) with advancing age. 19,53,65 Finally, Calder provides a good summary on the effects of aging for various ocular motor tests from numerous published reports, which are summarized in Table 1. 52 Overall, prolonged saccadic latencies and reduced smooth pursuit and OKN gains are observed in elderly patients when compared against younger adults.…”
Section: Ocular Motor Testingmentioning
confidence: 99%
“…We concentrated on the special case in which the monitor was positioned so that the axis of this rotation passed midway between the two eyes and the observer’s gaze was directed at the center of the display. This meant that, although the visual rotation was defined with respect to the head, each eye saw rotation about its optic axis, and many studies have shown that this induces torsional tracking of the two eyes in the direction of the seen rotation, often termed cycloversion (Cheung & Howard, 1991; Cheung, Money & Howard, 1995; Collewijn, van der Steen, Ferman & Jansen, 1985; Farooq, Gottlob, Benskin & Proudlock, 2008; Farooq, Proudlock & Gottlob, 2004; Houben, Goumans & van der Steen, 2006; Howard, Sun & Shen, 1994; Howard & Templeton, 1964; Ibbotson, Price, Das, Hietanen & Mustari, 2005; Kertesz & Jones, 1969; Lopez, Borel, Magnan & Lacour, 2005; Morrow & Sharpe, 1993; Seidman, Leigh & Thomas, 1992; Suzuki, Shinmei, Nara & Ifukube, 2000; Thilo, Probst, Bronstein, Ito & Gresty, 1999; van Rijn, van der Steen & Collewijn, 1992; 1994a; 1994b; Wade, Swanston, Howard, Ono & Shen, 1991; Washio, Suzuki, Sawa & Ohtsuka, 2005; Zupan & Merfeld, 2003). …”
Section: Introductionmentioning
confidence: 99%